The Use of Digital Guessing Game to Improve Students’ Speaking Ability - Ai Hayati (Journal of English Education and Teaching, 2020)
This study was investigated the effects of Digital Guessing Games strategy on students?  speaking ability of Islamic Senior High School students as well as to find out their perceptions of using it. In doing so, the subjects consisted of 44 students who were in tenth grade. Then they were divided into two equal experimental and control groups randomly (N=22). This study used explanatory sequential mixed-method whereas pre-test and post-test were administrated to collect quantitative and questionnaire was given to collect qualitative data.The experimental group was taught speaking using DGG application, whereas the control group using conventional guessing game. Analyzing the data through the independent sample t-test revealed the effectiveness of DGG application, the experimental group out performed the control group of speaking narrative text. Furthermore, an Islamic Senior High School students in Tasikmalaya had a positive attitude toward utilization of DGG application.